The role of leadership style and organizational culture in enhancing employee performance - Ginting, Erjayana; Nurhayati, Popong; Sukmawati, Anggraini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Employee performance is critical to the success of an organization, heavily influenced by leadership style and organizational culture. This study aims to measure the influence of transformational leadership style on organizational culture and its impact on improving employee at PT XYZ, a consulting firm specializing in Strategic Project Management across multiple sectors, including Oil & Gas, Energy, Chemicals, Industrial & Infrastructure (ECI), Financial Services, Telecommunications, and Property. A quantitative approach was adopted, utilizing SEM-PLS for data analysis. The research sample consisted of 220 employees of PT XYZ in Pekanbaru, selected using non-probability convenience sampling, with the criterion that participants had a minimum of one year of work experience. Data were collected through structured questionnaires. The results revealed that transformational leadership significantly enhances organizational culture (R² = 86.4%) and directly improves employee performance (R² = 76.3%). Additionally organizational culture positively mediates the relationship between leadership style and employee performance. Employees working in teams characterized by trust, openness to risks, and idea-sharing demonstrated significantly higher performance levels. This study highlights practical implications for organizations: implementing transformational leadership training programs and fostering team-oriented cultures can drive employee performance and align with strategic organizational goals. These findings serve as a basis for developing leadership strategies and cultural initiatives to optimize workforce potential.